Factors associated with perceived effectiveness of training among academics in Universiti Malaysia Sarawak - Wong, Moi Hua. (Universiti Malaysia Sarawak, UNIMAS, 2007)
This study was aimed at determining the perceptions of academics towards the effectiveness of training and the factors associate with the perception towards the training effectiveness. This study was conducted in a public university in Sarawak that is Universiti Malaysia Sarawak (UNIMAS). A survey methodology was used in collecting the data and 100 academics that have undergone the Postgraduate Diploma in Teaching and Learning were selected as the sample in this study. Statistical analysis such as frequency, percentage, t-test, ANOVA, Pearson Correlation and Linear Regression Analysis were used to analyze the data. This study reveals that 68% of the respondents possess positive perceptions towards the effectiveness of training. The findings also reveal insignificant difference among respondents with selected demographic characteristics in term of their perceptions towards the effectiveness of training. The findings of this study also reveal that there are significant relationships between respondents’ perceived effectiveness of training and trainee’s trainability ( r = 0.540, p = 0.000), trainer’s competency( r = 0.450, p = 0.000), training method ( r = 0.333, p = 0.000), training environment ( r = 0.434, p = 0.000) and management support ( r = 0.551, p = 0.000). Linear Regression Analysis also shows that the trainee’s trainability is the most dominant factor that influences the academics’ perceptions. Based on the findings of this study, it can be concluded that the Postgraduate Diploma in Teaching and Learning was perceived as effective, well accepted and favored by the academics attending the training program. Apart from this, trainee’s trainability needs to be given greater attention in assuring higher training effectiveness. It is recommended that the management and the human resource development department should put more effort to increase the trainees’ motivation and abilities before urging them to participate in the training program.